Comparative analysis of response modes for gold nanoparticle biosensor based on localized surface plasmon resonance - Lopatynskyi, A.; Lopatynska, O.; Chegel, V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
The theoretical comparison of possible response measurement techniques for a
biosensor based on localized surface plasmon resonance (LSPR) in spherical Au
nanoparticle was made. The methods for measuring LSPR response considered differed
in the treatment of the change of light extinction spectrum along the wavelength and
extinction coordinate axes upon the formation of dense biomolecular monolayer on the
surface of the sensitive element. In addition, the transformation of the extinction LSPR
band with increase of the nanoparticle radius from 5 to 125 nm was investigated towards
the optimization of LSPR response for dipolar and quadrupolar LSPR extinction peaks.
A novel method for the measurement of wavelength shift Htop⁺ was introduced and
demonstrated to be more effective for estimation of the LSPR biosensor response as
compared to commonly measured extinction peak shift Δλmax .These techniques were
proved to produce maximal LSPR response when large-size Au nanoparticle (with a
radius of 125 nm) was used as a sensitive element of biosensor. The preferable mode of
extinction difference measurement turned out to be Vright, which is carried out at a
wavelength of the extreme extinction spectrum derivative on a right slope of the LSPR
peak. For this method, optimal nanoparticle radii were found to be about 40 nm for the
dipolar LSPR peak and near 100-105 nm for the quadrupolar one.